Ethics Training for U.S. Military Leaders: Challenging the Conventional Approach. (12th September 2017) - Asencio, Hugo; Byrne, Theodore; Mujkic, Edin
Abstract : The U.S. military plays a fundamental role in protecting the United States and its national security interests. Given the nature of the combat and noncombat duties military personnel perform and the ethical dilemmas they face in doing so, it is fundamental that they be men and women of strong ethical competence. Providing effective ethics training to those serving in the U.S. military is crucial; particularly to senior leaders, as they create the environment in which subordinates perform their duties. Current ethics training for senior leaders in the U.S. military focuses on developing individual moral competence. This article argues for the need to complement such training with an approach focusing on developing individuals' capacity to create and sustain organizational environments in which ethical reflection and action are possible.